PISA 2015: student achievement in Norway: a comparison between native and immigrant students - Correia, David Aas (2019)
Student achievement is often considered a product of student background, school variables, and institutional setting. Literature also indicates that these educational inputs have varying effects on students. This dissertation performs an in-depth analysis of student achievement in Norway, using the data from PISA 2015, to see which educational inputs contributed to the fact that Norway performed better than the OECD average. The persisting achievement gap between native and immigrant students was also thoroughly researched. Student achievement was measured through two main channels: 1) characteristic effects, and 2) return effects, and these were elaborated using descriptive statistics, t-tests, educational production functions, and Blinder-Oaxaca decompositions. Results indicate that home possessions such as cultural items and books at home, student motivation and expectations, and parental background had significant positive impacts on student achievement, while significant negative effects were found for wealth items, study time outside of class, emotional support, student anxiety, and absenteeism. The school variables were not found very relevant for student achievement. Furthermore, immigrant students experienced significantly worse endowments, particularly for language, home possessions, and parental background, and this, together with experiencing worse returns than native students, helped to explain the negative differences between the groups.